Expression and activity of extracellular signal-regulated kinase-1/2 (ERK1/2) in normal tissues and human thyroid tumors - Guda, B. B.; Pushkarev, V. M.; Zhuravel, O. V.; Kovalenko, A.Ye.; Pushkarev, V. V.; Tarashchenko, Y. M.; Zurnadzhy, L. Y.; Kovzun, O. I.; Tronko, M. D. (Reports of the National Academy of Sciences of Ukraine, 2016)
We studied the expression and the activation of a main effector kinase of the mitogenic cascade — extracellular signal-regulated kinase 1/2 (ERK 1/2) — in normal tissues, benign and malignant human thyroid tumors. The total content of ERK in all investigated tumors except for goiter was significantly lower in tumor tissues compared with normal tissues. ERK activity was almost completely inhibited in tumors, but not in normal tissue. Thus, ERK activity is not associated with proliferative processes in a tumor tissue of a thyroid gland. Possible mechanisms of inhibiting the activity of the mitogenic signaling cascade in thyroid tumors are discussed.